Pelatihan Dasar Konseling Kristen bagi Guru Sekolah Minggu di Gereja Masehi Injili di Timor Zoar Penkase Oeleta - Pellondou, Yenry; Hutapea, Jusuf (Indonesia Christian Religion Theologians Association and Widya Agape School of Theology, 2025)
The community service activity aims to provide Basic Christian Counseling Training for Sunday School Teachers, carried out at GMIT Zoar Penkase Oeleta- Kupang City. This PkM is motivated by the awareness of Sunday school teachers about the importance of having counseling skills so that they are able to understand the situation of Sunday School children who are facing crises in their lives such as parental divorce, the death of an important person (for example, parents, siblings, grandparents or friends), serious illness, hospital admission, violence (physical, sexual, emotional), accidents, and trauma. This Community Service activity aims to provide understanding and basic counseling techniques to Sunday school teachers regarding the importance of sensitivity so that they can understand the problems faced by Sunday school children, with seminar and training methods. So, in the end this activity succeeded in educating Sunday school teachers with basic skills in counseling techniques, which they can then apply in mentoring and counseling activities for Sunday school children who are in problematic situations. Kegiatan Pengabdian kepada masyarakat bertujuan untuk memberikan Pelatihan Dasar Konseling Kristen bagi Guru Sekolah Minggu, dilaksanakan di GMIT Zoar Penkase Oeleta- Kota Kupang. PkM ini dilatarbelakangi oleh kesadaran guru sekolah minggu tentang pentingnya memiliki kemapuan konseling sehingga mampu memahami keadaan anak-anak Sekolah minggu yang sedang menghadapi krisis dalam kehidupannya seperti perceraian orang tua, kematian orang penting (misalnya, orang tua, saudara, kakek, nenek, atau teman), sakit keras, masuk rumah sakit, kekerasan (fisik, seksual, emosional), kecelakaan, dan trauma. Kegiatan Pengabdian Kepada Masyarakat ini bertujuan untuk memberikan pemahaman dan teknik konseling dasar kepada guru sekolah minggu terkait pentingnya kepekaan sehingga dapat memahami permasalahan yang dihadapi anak-anak sekolah minggu, dengan metode seminar dan pelatihan. Sehingga, pada akhirnya kegiatan ini berhasil mengedukasi guru sekolah minggu dengan keterampilan dasar dari teknik-teknik konseling, yang kemudian dapat mereka terapkan dalam kegiatan pendampingan dan konseling bagi anak-anak sekolah minggu yang berada dalam situasi problematik.